Peran Pembelajaran Sastra di Sekolah Dasar: Strategi Integratif untuk Memperkuat Kecerdasan Linguistik, Karakter, dan Emosional - Ismail Marzuki; Ahmad Rifai; Hani Agustina (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aims to analyze the role of children’s literature in lower-grade primary school learning, focusing on its influence on students’ verbal abilities, character development, and emotional growth. The research method used is a literature review, compiling and examining various relevant scholarly sources, including journal articles, academic books, digital library collections, and research findings published between 2020 and 2025. The review results indicate that children’s literature has a strategic contribution in supporting students’ cognitive, social, and emotional development. Literary works presented through creative, contextual, and locally based teaching materials can stimulate linguistic intelligence, strengthen character values, and facilitate children’s emotional maturity. These findings emphasize that integrating children’s literature into primary school learning not only enriches language competence but also serves as an effective medium for shaping students’ personality and emotional intelligence.